Basin modelling : practice and progress - Iliffe, J. E.; Düppenbecker, S. J. (Geological Society special publication, 1998)
Basin Modelling: Practice and Progress aims to focus on the application of basin modelling tools to real problems, and to share experiences as to which techniques have worked and which have not. Modelling is a valuable process of risk reduction in exploration prospectivity assessment. It is an area which has significant room for risk reduction in new technologies, or in better practices with existing technologies. The impact of basin modelling on the exploration business is on risking source effectiveness, and by providing the timing framework for petroleum generation, migration and reservoir/trap formation. The reconstruction of the geological evolution of a sedimentary basin, and numerical quantification of this information is now considered to add considerable value. Insight into the development and understanding of a basin that develops during a basin modelling study provides as much value as the final numerical results.